Fixed partial prosthesis: biomechanical analysis of stress distribution among three retention alternatives - Chica, Edwin; Latorre, Federico; Agudelo, Sergio (Revista Facultad de Odontología Universidad de Antioquia, 2010)
Introduction: the purpose of this study was to analyze the stress distribution among three retention alternatives used in a three unit fixed partial prosthesis, using the Finite Element Analysis (FEA). Methods: three tridimensional FEA models of the upper anterior area, restored with a cast post, another with a prefabricated post and the third one with an implant, were prepared. The models of the restored area consisted of trabecular bone, cortical bone, periodontal ligament, gingival, root, gutta-percha, resin luting cement, post, composite resin core (for prefabricated posts), metallic core and metal ceramic crown. The post materials considered for analysis were a noble casting alloy and fiber glass. The posts were cemented with resin luting cement. A lineal analysis was carried out and the nonlinearities associated with the geometry of the model, were considered. The variables included in the model were the modulus of elasticity and Poisson´s ratio. An increasing load of 1N was applied on the lingual surface of the crown with an inclination of 45°. Von Mises stress were then calculated. Results: the Finite Element Analysis showed that the distribution of stresses generated on the tooth modeled with posts, decreased significantly, in accordance with an inverse proportional relation with the modulus of elasticity of the material. In the implant model, the stresses concentrated on the cervical area and on the implant itself. Conclusions: within the limitations of this study, it was found that that there were marked differences in relation with the stress distribution among the three retention alternatives, where the system with different rigidity components is loaded, the most rigid element is capable of resisting the highest stress without distortion.